The relationship between family support and the level of distress in type 2 diabetes mellitus patients - Susanti, Yuli (JOURNAL OF Mental Health Concerns, 2026)
Background: Diabetes mellitus is a chronic disease with an increasing number of sufferers each year. Diabetes without comprehensive treatment not only affects physical health but also affects the mental health of sufferers, including diabetes distress. Diabetes distress can affect the quality of life of sufferers if not treated properly. Education on self-care management and social support, especially from family, can improve patients' clinical outcomes, psychosocial well-being, and decision-making abilities. The role of family support as a support system and collaborator in healthcare contributes to increased self-efficacy in self-care and can reduce distress levels for diabetes patients. Purpose: To determine the relationship between family support and distress levels in patients with type 2 diabetes mellitus. Method: This study was conducted in July 2025 using descriptive quantitative research. The respondents in this study consisted of 30 type 2 diabetes mellitus patients who visited the Lesteri Mulyo 3 Health Center in Dukuh Joholor Triyagan Mojolaban Sukoharjo, Central Java. The technique used in this study was accidental sampling, and the instruments used were a demographic data questionnaire, a diabetes distress scale questionnaire, and a Hensarling Diabetes Family Support Scale (HDFSS) questionnaire. Data analysis in this study used the Chi-Square test. Results: Most respondents received good family support. Based on the results of the family support relationship analysis test, a p-value of 0.01 was obtained. A significance value of less than 0.05 means that the research hypothesis states that there is a significant relationship between family support and the level of distress in diabetes patients. Conclusion: Family support significantly affects the level of distress in patients with type 2 diabetes mellitus. Keywords: Diabetes Distress; Family Support; Type 2 Diabetes Mellitus.